The black scourge? Race and the Rockefeller Foundation’s tuberculosis commission in interwar Jamaica - Henrice Altink (História, Ciências, Saúde: Manguinhos)
From 1927 to 1942, the Rockefeller Foundation ran a tuberculosis commission in Jamaica that researched the epidemiology of the disease, examined the efficacy of a vaccine with heat-killed tubercle bacilli, and offered basic treatment to tuberculosis sufferers. Drawing upon diaries and scientific writings by the staff employed by the commission, among other sources, this article explores the role that race played in the tuberculosis commission. It assesses how race shaped the research conducted by the commission, how it informed staff interactions and staff/patient relations, and the clash and/or confluence of “imported” and local racial ideas in the commission’s work.